B 2007: Formal Specification and Development in B 7th International Conference of B Users, Besancon, France, January 7-19, 2007, Proceedings - Julliand, Jacques; Kouchnarenko, Olga (Programming and Software Engineering,, 2006)
TheseproceedingsrecordthepaperspresentedattheSeventhInternationalC- ference of B Users (B 2007), held in the city of Besan¸ con in the east of France. This conference was built on the success of the previous six conferences in this series, B 1996, held at the University of Nantes, France; B 1998, held at the University of Montpellier, France; ZB 2000, held at the University of York, UK; ZB 2002, held at the University of Grenoble, France; ZB 2003, held at the U- versity of Turku, Finland; ZB 2005 held at the University of Surrey, Guildford, UK. B 2007 was held in January at the University of Franche-Comt´ e,Besan¸ con, France, hosted by the Computer Science Department (LIFC). LIFC has always placed particular emphasis on the applicability of its research and its relati- ship with industrial partners. In this context, it created in 2003 a company called LEIRIOS Technologies, which produces an automatic test generator tool (LTG) frommodels described in the B speci?cationlanguage. Other members of LIFC work on extensions of the B method for specifying and verifying dynamic properties. All the submitted papers in these proceedings were peer reviewed by at least three reviewers drawn from the B committee, depending on the subject matter of the paper. The authorsof the papersforB 2007werefrom Australia,Canada, Finland, Germany, France, Switzerland, and the UK. The conference featured a rangeof contributions by distinguished invited speakers drawn from both ind- try and academia.